2014
DOI: 10.3892/ol.2014.2256
|View full text |Cite
|
Sign up to set email alerts
|

Serum secreted frizzled-related protein 5 levels differentially decrease in patients with hepatitis B virus-associated chronic infection and hepatocellular carcinoma

Abstract: The aim of this study was to investigate the characteristics of serum secreted frizzled-related protein 5 (SFRP5), an inhibitor of Wnt signaling, in hepatitis B virus (HBV)-associated infections and hepatocellular carcinoma (HCC) patients. Serum SFRP5 levels were detected in 147 patients with HBV-associated chronic infection or HCC. Compared with the non-HBV-infected and non-HCC group, the HBV-associated chronic infection and HCC groups exhibited decreased serum SFRP5 levels. A significant inverse correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…Coherently, restoration of sFRP1 expression could be achieved by DNA demethylation and exogenous sFRP1 reverses the functional effects observed indicating that downregulation of sFRP1 through DNA hypermethylation augments Wnt/β-catenin signaling in HCC. Besides, sFRP1/3/5 was revealed to be downregulated in two independent HCC cohorts [75,76]. Given the mechanism between sFRPs and Wnt/FZDs on the alteration of the Wnt signaling pathway, downregulation of sFRPs in HCC suggests that Wnt signaling is activated in response to Wnt/FZD binding.…”
Section: Mechanism Of Deregulated Fzds In Hccmentioning
confidence: 99%
“…Coherently, restoration of sFRP1 expression could be achieved by DNA demethylation and exogenous sFRP1 reverses the functional effects observed indicating that downregulation of sFRP1 through DNA hypermethylation augments Wnt/β-catenin signaling in HCC. Besides, sFRP1/3/5 was revealed to be downregulated in two independent HCC cohorts [75,76]. Given the mechanism between sFRPs and Wnt/FZDs on the alteration of the Wnt signaling pathway, downregulation of sFRPs in HCC suggests that Wnt signaling is activated in response to Wnt/FZD binding.…”
Section: Mechanism Of Deregulated Fzds In Hccmentioning
confidence: 99%
“…Only the anti-apoptotic HAX1 was upregulated in the common termination pathway, known to repress autocleavage of pro-caspase 9 (Han et al 2006). Thus, our analysis at the transcriptome level indicates that SFRP5 is affecting pro-and antiapoptotic pathways, which may support SFRP5's role in tissue homeostasis regulation, which was already displayed in several cancer types (Zhao et al 2009;Peng et al 2014;Gutiérrez-Vidal et al 2015).…”
Section: Successful Sfrp5 Overexpression In Hek293t and Hipsc-cmssupporting
confidence: 68%
“…Multiple functions and interactions of SFRP5 were reported. In several tissues SFRP5 is described as fundamental for tissue homeostasis, because it has been shown that its expression is altered in different diseases and cancers (Zhao et al 2009;Peng et al 2014;Gutiérrez-Vidal et al 2015). For example SFRP5 is a known tumor suppressor gene in many cancer types e.g.…”
Section: Wnt Pathway In Cardiac Remodeling and Heart Failurementioning
confidence: 99%
“…The Frizzled (FZD) family is transmembrane receptors of Wnt signaling pathway, consisting of 10 isoforms (FZD1-10) [ 7 , 8 ]. FZDs are reported to be involved not only in embryogenesis and development but also in tumor development and progression [ 9 , 10 ]. FZD2 was over-expressed in hepatocellular carcinoma (HCC) and head and neck squamous cell carcinoma compared to paracancerous tissues and significantly associated with the survival of patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%